KONTRIBUSI KEARIFAN LOKAL DAN ETIKA BUDDHA DALAM PERSPEKTIF KEPEMIMPINAN MODERN - Mulyana Mulyana (STABN Sriwijaya, 2014)
Centre of Java have various local wisdom, one of them related to leadership sud: as Sera/ W11la11g Reh and Asta Brnta Teaching. Beside that, Budd/m's Teaching in text Jatnka also concern 011 leadership, called Dasa Raja Dhamma. This article aim to study the contribution of local wisdom, specially Serat W11la11g Rel, and Asta Brata Teaching mid Buddhist Ethics, specially Dasa Raja Dhamma 011 leadership patten, iu modem era. This research use the qualitatiue approach and libra,y research method